SOME FATTY ACID AND SEMEN CHARACTERISTICS OF HOLSTEIN BULLS AS INLUENCED BY DIFFERENT SPERM FREEZABALITY - S. M. Eidan; R. I. Khalil; A.F.Naser (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was conducted to investigate the relationship between the concentration of some fatty acids in seminal plasma and semen characteristics of Holstein bulls with different sperm freezabilities. The semen straws that cryopreserved for two years were divided into three groups according to the sperm’s freezability: medium (MF,73.02%), good (GF,83.76%), and high (HF,91.20%). The sperm’s cell individual motility (SCIM) in fresh semen was superior (P≤0.05) in bulls with MF and GF as compared with HF bulls. Concomitantly, the HF bulls were significantly (P≤0.05) superior to those MF bulls in total fatty acid concentrations. Moreover, HF bulls recorded lesser (P≤0.05) DNA damage percentage as compared with those of GF bulls. The differences among the three groups in concentrations of some fatty acid and SCIM at 48 hours and two years post-cryopreservation lacked significance. In conclusion, greater SCIM in bull’s fresh semen recorded the lowest freezability, which indicated more sensitivity to freezing conditions and may reflect fertilizing ability of these bulls.